02 Semantic relations among the greek borrowings in albanian language - Sofia DELIGIORGI (Association of Social and Educational Innovation, 2015)
The borrowings from Greek into Albanian have entered at different times, for one reason or another and in different circumstances. They are found in the entire lexical structure of Albanian language, almost in all the layers and the paradigmatic groups of the words, and even in the idiomatic expressions. The borrowings from Greek into Albanian as well as the borrowings from the other languages change according to the morphological patterns of this language. Later, over the time, they change and develop further more getting, apart from the denotative values, even other important values, such as: semantic values, emotive values, stylistic values, syntagmatic values, paradigmatic values, word-formation values, or substitutive values.